Implementasi Manajemen Pesantren dalam Membentuk Karakter Santri di Pondok Pesantren Miftahul Jannah Kecamatan Cigugur - Dede Asiah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This research aims to analyze the implementation of Islamic boarding school management in an effort to shape the character of students. Effective Islamic boarding school management is expected to have a significant impact on the character development of students, which is the main goal of education at this institution. This research uses a qualitative approach with a case study method in representative Islamic boarding schools. Data collection techniques were carried out through in-depth interviews, participant observation and document analysis. The research results show that good Islamic boarding school management includes structured curriculum planning, consistent moral development, and active involvement of caregivers in the daily activities of the students. The implementation of effective management not only has an effect on improving the quality of education, but also on strengthening religious and social values ??within students. These findings provide insight into the importance of integrated management in creating an environment that supports the holistic character development of students. It is hoped that this research can be a reference for Islamic boarding school managers and stakeholders in improving the quality of educational management in Islamic boarding schools.